DAMPAK PERUBAHAN PENGGUNAAN LAHAN DI UB FOREST TERHADAP KARBON BIOMASSA MIKROBA DAN TOTAL POPULASI BAKTERI - Irma Ardi Kusumawati; Cahyo Prayogo (Jurnal Tanah dan Sumberdaya Lahan, 2019)
UB Forest is one example of forest ecosystems that are closely related to carbon cycle. However, the change of use of forest land into agricultural land in the forest can cause a negative impact on the environment, including reduced carbon reserves and decrease soil fertility, indicated by the reduced population of microbial activity and soil macrofauna. This study was aimed to explore effects of lang use change on microbial biomass and bacteria and bacterial population in the UB forest. The observation plot was determined based on land use, i.e., MK (mahogany 40 years and coffee 2-4 years), PK1 (pine 20 years and coffee 4-6 years), PK2 (pine 30 years and coffee 2- 4 years), PS (pine 40 years and cabbage), PM (pine 20 years and shrubs), MT (mahoni 40 years and taro), PK4 (pine 40 years and coffee 3-5 years) PK3 (pine 35 years and coffee 5-8 years). Observations were repeated 3 times, resulting in 24 plots. The extent of land area observed was 20 m x 20 m, including there was litter trap of 1 m x 3 m for observation of litter input dynamics. Vegetation observations and analyzes included in-situ litter weight, dry weight of litter per two weeks, dry weight of understorey, and polyphenol and lignin contents. Soil sampling was collected for analyses of C-organic, pH, microbial biomass, and total population of bacteria. The results showed that the highest values of microbial biomass carbon and total population of bacteria was found on PK3 land. The high microbial biomass carbon of 55,48 mg / kg-1 and total population of bacteria of 10.1 x 10-6 cfu/ml-1 had positive correlation and are influenced by litter input, understorey, C-organic content, soil pH, and litter quality in the form of polyphenols and lignin.